Associations of dietary markers with brain volume and connectivity: a systematic review of MRI studies - Jensen, DEA; Leoni, V; Klein-Flügge, MC; Ebmeier, KP; Suri, S (Elsevier, 2021)
The high prevalence of unhealthy dietary patterns and related brain disorders, such as dementia, emphasizes the importance of research that examines the effect of dietary factors on brain health. Identifying markers of brain health, such as volume and connectivity, that relate to diet is an important first step towards understanding the lifestyle determinants of healthy brain ageing. We conducted a systematic review of 52 studies (total n = 21,221 healthy participants aged 26–80 years, 55 % female) that assessed with a range of MRI measurements, which brain areas, connections, and cerebrovascular factors were associated with dietary markers.